1997
DOI: 10.1016/s1090-3801(97)90051-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of topical anaesthesia methods for venous cannulation in adults

Abstract: A prospective, randomized clinical trial was performed in order to assess the efficacy and side-effects of commonly used topical anaesthesia methods in adults receiving peripheral venous cannulation. The study was double-blinded to the degree that the methodologies allowed. One hundred and fifty healthy adults undergoing elective surgery were allocated at random to five groups: EMLA cream, ethyl chloride spray, intracutaneous infiltration with 2% lidocaine, placebo cream and no treatment. Venipuncture was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 15 publications
(16 reference statements)
1
49
1
Order By: Relevance
“…11,12 Few studies have examined local or systemic complications, including infection, resulting from local or topical anaesthetic use. Biro et al 1 reported immediate local side effects when comparing no treatment, placebo, a eutectic mixture of local anaesthetics (EMLA), ethyl chloride spray and lignocaine infiltration following successful cannulation. Although there were no significant differences between the groups, no longer-term follow-up was undertaken.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11,12 Few studies have examined local or systemic complications, including infection, resulting from local or topical anaesthetic use. Biro et al 1 reported immediate local side effects when comparing no treatment, placebo, a eutectic mixture of local anaesthetics (EMLA), ethyl chloride spray and lignocaine infiltration following successful cannulation. Although there were no significant differences between the groups, no longer-term follow-up was undertaken.…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining other spray applications, such as ethyl chloride, prior to cannulation have not investigated the potential risk of skin contamination. 1,3,4 However, there is one report of the bactericidal effect of ethyl chloride. Burney et al 13 found that a fine spray of ethyl chloride on to agar plates inoculated with bacteria reduced the bacterial count significantly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,9 Could it be that doctors accept the efficacy of local anaesthetic but do not use it because the pain of cannulation is not thought bad enough to warrant the extra hassle? My own impression from observing and talking to other doctors, supported by the findings of Sado and Deakin and others, 1,11 is that this accounts for part of their reluctance-the pain of cannulation is considered regrettable but a fact of life (no pain, no gain). But another factor, as many have found, is simple ignorance: they are unaware of the evidence and nobody has ever taught them to use local anaesthesia for these procedures.…”
mentioning
confidence: 88%
“…On p. 158 Dr Sado and Dr Deakin 1 report on doctors' use of local anaesthesia for venous cannulation and find that little has changed in a decade: 2 very few ward doctors routinely use local anaesthesia for cannulation, despite an abundance of evidence that it makes the procedure much more bearable (the same is true of arterial puncture, but here I focus on venous cannulation because it is so much more common). The unanimous conclusion of those who have investigated the matter is that patients and volunteers find the pain of local anaesthetic infiltration less than that of cannulation, [3][4][5][6][7][8][9][10][11][12] even with cannulae as small as 20 gauge, and cannulation is not made more difficult by the procedure. 6,9 Could it be that doctors accept the efficacy of local anaesthetic but do not use it because the pain of cannulation is not thought bad enough to warrant the extra hassle?…”
mentioning
confidence: 99%